Evolutionary history of a Scottish harbour seal population - Nikolic, Natacha; Thompson, Paul; de Bruyn, Mark; Macé, Matthias; Chevalet, Claude (PeerJ, 2020)
Efforts to conserve marine mammals are often constrained by uncertainty over their population history. Here, we examine the evolutionary history of a harbour seal (Phoca vitulina) population in the Moray Firth, northeast Scotland using genetic tools and microsatellite markers to explore population change. Previous fine-scale analysis of UK harbour seal populations revealed three clusters in the UK, with a northeastern cluster that included our Moray Firth study population. Our analysis revealed that the Moray Firth cluster is an independent genetic group, with similar levels of genetic diversity across each of the localities sampled. These samples were used to assess historic abundance and demographic events in the Moray Firth population. Estimates of current genetic diversity and effective population size were low, but the results indicated that this population has remained at broadly similar levels following the population bottleneck that occurred after post-glacial recolonization of the area.
Keywords: Evolution; Genetic; Seal